Molecular genetics of polyunsaturated fatty acid biosynthesis in marine bacteria - Smith, MC (2002)
This study investigated the genetics of polyunsaturated fatty acid (PUF A) production from two bacterial species isolated from Antarctic sea ice (Shewanella gelidimarina and Colwellia psychrerythraea) with a view to evaluate the use of PUFA genes as molecular markers in culture independent studies. Initial attempts to utilise transposon mutagenesis to determine the loci of PUFA production within these organisms was unsuccessful. However, utilising PCR mediated amplification, a number of regions from S. gelidimarina with high homology to pfaA, pfaC and pfaD from the published eicosapentaenoic (EPA) gene cluster of Shewanella sp. strain SCRC 2738 were resolved. Similarly, this study identified an open reading frame (ORF) encoding a 4' phosphopantetheinyl transferase (pfaE) with high predicted protein homology but low nucleotide similarity to its homolog from strain SCRC 2738, indicating a divergence in codon usage between the two ORFs. Two amplified regions from S. gelidimarina with homology to internal regions of pfaA and pfaD were chosen for use as molecular probes to examine the distribution of PUF A genes across phylogenetic boundaries. A number of non-PUFA (PUFA-) producing species from the genera Shewanella and Psychromonas were shown to contain genes with homology to both probes. However, transcription of the putative PUFA genes could not be detected in PUFA- species. This study also represents the first known report of PUFA production within two isolates from the genus Psychromonas. The distribution of pfa-like genes within the family Alteromonadaceae may indicate that the progenitor of the group had the ability to produce PUFA and that the ability has been lost on a number of occasions. Analysis of the G+C content and G+C content at the synonymous third codon position of published pfa genes from Shewanella sp., Moritella marina and Photobacterium profundum indicates that pfa genes may have undergone horizontal gene transfer from the Alteromonadaceae to the Vibrionaceae. Southern blot analysis indicated the presence of one allele of pfaA and pfaD within the C. psychrerythraea genome. However, based on information gained from sequence analysis of a genome library from C. psychrerythraea and RNA/DNA hybridisation studies it is evident that these ORFs are not functional. Similarly, other members of the genus Colwellia, were shown not to contain functional homologs of ·pfaA or pfaD suggesting that some members of the genus Colwellia contain _a novel/ divergent genetic mechanism for the biosynthesis of PUFA.